2020
DOI: 10.1101/2020.02.28.970053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal learning among prefrontal and striatal ensembles

Abstract: 1Behavioral flexibility requires the prefrontal cortex and striatum. Here, we investigate neuronal 2 ensembles in the medial frontal cortex (MFC) and the dorsomedial striatum (DMS) during one 3 form of behavioral flexibility: learning a new temporal interval. We studied corticostriatal 4 neuronal activity as rodents trained to respond after a 12-second fixed interval (FI12) learned to 5 respond at a shorter 3-second fixed interval (FI3). On FI12 trials, we discovered time-related 6 ramping was reduced in the M… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 59 publications
7
9
0
Order By: Relevance
“…Our findings are broadly consistent with our previous work (Emmons et al., 2016, 2017, 2019, 2020). In one of these studies with well‐trained animals (Emmons et al., 2020), we found that striatal time‐related ramping was stable as highly trained rats learned a new, shorter fixed interval over 3 days. By contrast, in this study, we compared striatal temporal encoding just after mice acquired a switch interval timing task and again after ~10 days of experience.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are broadly consistent with our previous work (Emmons et al., 2016, 2017, 2019, 2020). In one of these studies with well‐trained animals (Emmons et al., 2020), we found that striatal time‐related ramping was stable as highly trained rats learned a new, shorter fixed interval over 3 days. By contrast, in this study, we compared striatal temporal encoding just after mice acquired a switch interval timing task and again after ~10 days of experience.…”
Section: Discussionsupporting
confidence: 94%
“…Hence, animals may have habituated with the action (nose poking), and the only new contingency introduced in the task was the wait time. In this sense, our results agree with previous results implicating the mPFC in top-down control of executive tasks, including behavioral switching learning 2831 .…”
Section: Discussionsupporting
confidence: 93%
“…Finally, our results agree with recent neuronal recordings during learning of a new interval in a fixed-interval task28. They showed that the medial prefrontal cortex and striatum play different rules on temporal and behavior flexibility.…”
Section: Discussionsupporting
confidence: 92%
“…We conjecture that the appearance of the visual target initiates the first ramping activity, timing the interval until SSRT. This can provide a substrate for fronto-striatal pathways to learn, update, or validate the temporal structure of the task 5557 .…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to clarify this projection. Also, these neurons can contribute to fronto-striatal pathways to learn and update the temporal structure of the task 57,58,59 . Axon terminals from SEF are dense in the caudate nucleus 43 , arising from pyramidal neurons in L3 and L5 60,61,62 .…”
Section: Time Estimation and Goal Maintenance The Interpretation Of The Other Two Classes Ofmentioning
confidence: 99%